Diversity‐Oriented Synthesis of Spirocyclohexene Indane‐1, 3‐diones and Coumarin‐Fused Cyclopentanes via an Organobase‐Controlled Cascade Reaction. Issue 16 (14th July 2020) - Wang, Min; Tseng, Ping‐Yao; Chi, Woei‐Jye; Suresh, Sundaram; Edukondalu, Athukuri; Chen, Yi‐Ru; Lin, Wenwei
Abstract: An organobase‐controlled, divergent cascade reaction to construct spirocyclohexene indane‐1, 3‐diones and coumarin‐fused cyclopentanes is reported. The cascade reaction is triggered by the 1, 6‐addition of 3‐homoacylcoumarins to the indanedione‐derived acceptors and further regio/chemoselective reaction that preferentially resulted in spiro systems and fused cyclopentanes in a diversity‐oriented manner. The 1, 6‐addition/aldol and 1, 6‐addition/vinylogous Michael addition cascade processes were controlled by different base/solvent systems to the predominant formation of one of the two carbocyclic compounds. Abstract :